Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12031-017-0992-z
|View full text |Cite
|
Sign up to set email alerts
|

New Data from Pdfgb ret/ret Mutant Mice Might Lead to a Paradoxical Association Between Brain Calcification, Pericytes Recruitment and BBB Integrity

Abstract: Data of mice with PDGF-B-truncating mutation (Pdgfb ) from different research groups indicate that the malfunction of this protein leads to reduced pericyte recruitment, loss of Blood-Brain Barrier (BBB) integrity and bilateral brain calcification. This makes these mice important models for Primary Brain Calcification and pericyte-BBB correlation studies. The global brain pericyte count is reduced in Pdgfb mice, with higher BBB permeability. We have overlapped the data from other research groups into a figure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Only Pdgfb ret/ret mice, in which the tissue distribution of PDGF-B is altered, probably due to the loss of a proteoglycan-binding motif, develop brain calcification (Keller et al, 2013;Vanlandewijck et al, 2015;Nikolakopoulou et al, 2017;Nahar et al, 2020). Inexplicably, the EC permeability was higher in the noncalcification-prone than in the calcification-prone brain areas; this region-specific heterogeneity in permeability was not associated with cell junction proteins or pericyte loss (Moura et al, 2017;Villasenor et al, 2017). MYORG encodes an endoplasmic reticulum-localized α-glucosidase that is specifically expressed in astrocytes, and its functional defects also cause brain calcification (Vanlandewijck et al, 2018;Yao et al, 2018;Meek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Only Pdgfb ret/ret mice, in which the tissue distribution of PDGF-B is altered, probably due to the loss of a proteoglycan-binding motif, develop brain calcification (Keller et al, 2013;Vanlandewijck et al, 2015;Nikolakopoulou et al, 2017;Nahar et al, 2020). Inexplicably, the EC permeability was higher in the noncalcification-prone than in the calcification-prone brain areas; this region-specific heterogeneity in permeability was not associated with cell junction proteins or pericyte loss (Moura et al, 2017;Villasenor et al, 2017). MYORG encodes an endoplasmic reticulum-localized α-glucosidase that is specifically expressed in astrocytes, and its functional defects also cause brain calcification (Vanlandewijck et al, 2018;Yao et al, 2018;Meek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we knocked out retention motif of PDGF-B, which is the binding site of PDGF-B with the extracellular matrix [16]. Previous studies demonstrated that PDGF-B ret/ret mice suffered cerebral vascular dysfunction by pericyte recruitment deficiency and subsequent breach on the blood-brain barrier after SAH [4,[17][18][19][20]. Similarly, the pericytes were covered with 26-40% microvessels in mature lungs [21], which might also be regulated by PDGF-B in the pathophysiological progression after SAH to cause pulmonary edema, previously considered to be neurogenic [22].…”
Section: Discussionmentioning
confidence: 99%
“…PDGFRβ ret/ret mice are an important experimental models for studying pericyte function. Compared with wild-type mice, they had significantly fewer pericytes in their brain capillaries (Moura et al 2017 ). To clearly determine the relationship between TIMP-3 and pericyte, we used PDGFRβ ret/ret mice as experimental subjects.…”
Section: Methodsmentioning
confidence: 99%